Applications of Self-Determination Theory and Self-Regulation Strategies in Exercise Programs for Smoking Cessation - Tzatzaki Θεοδώρα; Pappa Βασιλική; Apostolou Λεβάντα; Hatzigeorgiadis Αντώνης; Theodorakis Γιάννης (Inquiries in Physical Education and Sport, 2016)
The volume of studies examining the effects of exercise interventions for smoking cessation is progressively increasing. The purpose of the present article was to present the development and application of an exercised-based smoking cessation intervention on the principles of the self-determination theory and selfregulation. According to the self-determination theory, when three basic psychological needs are satisfied (autonomy, competence, and relatedness), then the individual is more likely to engage in changing a specific behavior. In this program, individuals could select the type, the place and time of the exercise, were guided on attaining goals regarding the duration and frequency of exercise, as well as their smoking habits, and received daily support from personal trainers. In addition, during the program, participants were trained on specific self-regulation strategies (goal setting, self-talk, breathing and delay techniques) in relation to their exercising and smoking to further assist the adherence of exercise behavior towards the ultimate goal of smoking cessation.